2017
DOI: 10.1002/cpdd.383
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Safety of Ozanimod, a Novel Sphingosine‐1‐Phosphate Receptor Modulator: Results of a Thorough QT/QTc Study

Abstract: Ozanimod is a novel, selective, oral sphingosine‐1‐phosphate (1 and 5) receptor modulator in development for multiple sclerosis and inflammatory bowel disease. This randomized, double‐blind, placebo‐controlled, positive‐controlled, parallel‐group thorough QT study characterized the effects of ozanimod on cardiac repolarization in healthy subjects. Eligible subjects were randomized to 1 of 2 groups: ozanimod (escalated from 0.25 to 2 mg over 14 days) or placebo (for 14 days). A single dose of moxifloxacin 400 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…A third S1P receptor modulator, ozanimod, binds selectively with high affinity to receptor subtypes 1 and 5 and is undergoing regulatory assessment for the treatment of MS. A Phase 1 cardiac safety study in 145 healthy adults showed that although ozanimod blunted the observed diurnal increase in HR, excursions below pre-dose HR were no greater than with placebo. Ozanimod did not prolong the QTc interval or cause clinically significant bradycardia, suggesting a favourable cardiac safety profile [72]. In the Phase 2 RADIANCE study (n = 258), the maximum reduction in mean HR by Holter monitoring during the first 6 h in ozanimod-treated participants was <2 bpm compared with baseline, with no patient having a minimum hourly HR < 45 bpm.…”
Section: Ozanimodmentioning
confidence: 94%
“…A third S1P receptor modulator, ozanimod, binds selectively with high affinity to receptor subtypes 1 and 5 and is undergoing regulatory assessment for the treatment of MS. A Phase 1 cardiac safety study in 145 healthy adults showed that although ozanimod blunted the observed diurnal increase in HR, excursions below pre-dose HR were no greater than with placebo. Ozanimod did not prolong the QTc interval or cause clinically significant bradycardia, suggesting a favourable cardiac safety profile [72]. In the Phase 2 RADIANCE study (n = 258), the maximum reduction in mean HR by Holter monitoring during the first 6 h in ozanimod-treated participants was <2 bpm compared with baseline, with no patient having a minimum hourly HR < 45 bpm.…”
Section: Ozanimodmentioning
confidence: 94%
“…All Holter data were transmitted to the ECG core laboratory (Bioclinica Inc, Princeton, NJ, USA) over the internet through a secure transfer program. The 12-lead ECGs were extracted automatically in triplicates at the following nominal time points on days -1, 1, 5, 8, and 28 just before pharmacokinetic (PK) sample collections (except on day -1 with no PK samples): prior to dosing (0 hour) and at 1,2,4,6,8,10,12,14,16, and 24 hours after dosing. The subject was rested in the supine position for the first 5 minutes before extractions and then 10 minutes during extractions.…”
Section: Ecg and Pk Collectionsmentioning
confidence: 99%
“…The proarrhythmic risk of ozanimod was previously evaluated in a thorough QT (TQT) study. 8 Following a 14-day titration regimen of QD oral doses of ozanimod 0.23 mg for 4 days, 0.46 mg for 3 days, 0.92 mg for 3 days, and 1.84 mg for 4 days in healthy subjects, no evidence of clinically significant QTc prolongation was observed, as demonstrated by the upper boundary of the 90% confidence interval (CI; two-sided) for the time-matched, placebo-corrected, baselineadjusted mean QTc (ΔΔQTc) being below the 10 msec threshold for both ozanimod 0.92 and 1.84 mg. The TQT study was conducted early during the clinical development and before the human mass balance study, which identified the active metabolites CC112273 and CC1084037.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews published in 2005 by Strnadova and 2011 by Satin and colleagues capture respective “snapshots in time” in this field. References to examples of individual TQT studies and related considerations are provided …”
Section: Technical Challenges In Conducting a Tqt Studymentioning
confidence: 99%
“…References to examples of individual TQT studies and related considerations are provided. [35][36][37][38][39][40][41][42]…”
Section: Technical Challenges In Conducting a Tqt Studymentioning
confidence: 99%